Crystal structure of bromidopentakis(tetrahydrofuran-κO)magnesium bis[1,2-bis(diphenylphosphanyl)benzene-κ2P,P′]cobaltate(−1) tetrahydrofuran disolvate - Patience B. Girigiri; Stephanie H. Carpenter; William W. Brennessel; Michael L. Neidig (Acta Crystallographica Section E: Crystallographic Communications, 2019)
Structural characterization of the ionic title complex, [MgBr(THF)5][Co(dpbz)2]·2THF [THF is tetrahydrofuran, C4H8O; dpbz is 1,2-bis(diphenylphosphanyl)benzene, C30H24P2], revealed a well-separated cation and anion co-crystallized with two THF solvent molecules that interact with the cation via weak C—H...O contacts. The geometry about the cobalt center is pseudotetrahedral, as is expected for a d10 metal center, only deviating from an ideal tetrahedral geometry because of the restrictive bite angles of the bidentate phosphane ligands. Three THF ligands of the cation and one co-crystallized THF solvent molecule are each disordered over two orientations. In the extended structure, the cations and THF solvent molecules are arranged in (100) sheets that alternate with layers of anions, the latter of which show various π-interactions, which may explain the particular packing arrangement.